Improving problem-solving ability and collaboration skills of ecosystem material through STEM integrated project-based learning - Ningrum, Teza Lestari; Wahidin, Wahidin; Diella, Dea (STKIP Persada Khatulistiwa Sintang, 2024)
The learning process at Cipasung Islamic High School is still teacher-centered so the formation of 21st century skills in students is still neglected. The purpose of this study was to determine the effect of the STEM-integrated project-based learning model on the problem-solving ability and collaboration skills of students on ecosystem material. This research was conducted in May 2023. The research method used is an experimental method with a Quasi Experiment design and the matching-only posttest-only control group design form. The research population was the X MIPA class of Cipasung Islamic High School in the 2022/2023 school year. The sample was taken using a purposive sampling technique and obtained X MIPA 1 class as the control class and X MIPA 4 as the experimental class. The research instruments used in this study consisted of 3 validated instruments, namely the problem-solving ability test instrument, the CSAT (Collaboration Self-Assessment Tool) questionnaire, and the collaboration skills observation sheet. The data analysis technique used is One way ANOVA test. Based on the results of the analysis, it can be concluded that there is an effect of STEM integrated project-based learning model on problem-solving ability and collaboration skills of students on ecosystem material in Class X MIPA SMA Islam Cipasung.